Corrosion-resistant EVA packaging adhesive film
By adding acid removers such as magnesium hydroxide and polycarbodiimide to the EVA film, the corrosion and potential-induced attenuation of EVA film in high temperature and high humidity environments are solved, and the corrosion resistance and permeability of the film are improved. Light rate ensures its long-term stability.
Patent Information
- Application Number
- CN202411394923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
During long-term use of EVA films, such as degradation, discoloration, fading, delamination, acetic acid and corroding electrodes, etc., especially in high temperature and high humidity environments, hydrolysis reactions lead to potential-induced attenuation and corrosion problems.
The formulation of corrosion-resistant EVA encapsulation films, including ethylene-vinyl acetate copolymer, crosslinking agent, antioxidant, light stabilizer, silane coupling agent and acid remover, is adopted by a single screw extrusion mechanism at 95°C. Preparation: Add acid removers such as magnesium hydroxide and polycarbodiimine to reduce the acetic acid content and improve the film's moisture and heat aging resistance.
It significantly reduces the acetic acid content of the encapsulated adhesive film after moisture and heat aging, improves the corrosion resistance and light transmittance of the adhesive film, avoids potential-induced attenuation and corrosion problems, and ensures the long-term stability of the adhesive film.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic component packaging, in particular to a corrosion-resistant EVA packaging adhesive film. Background Art
[0002] EVA film for solar cell encapsulation is a thermosetting film with EVA resin as base material, various additives added, and extruded by screw extruder. It has the characteristics of anti-wet heat aging, high peel strength, low potential induced decay, etc. It is mainly used for the encapsulation of solar cell modules, which can prevent water vapor penetration, high and low temperature resistance, and UV aging resistance, so as to ensure the long-term stable and efficient use of the battery modules.
[0003] During long-term outdoor use, EVA film will degrade, and aging phenomena such as discoloration, fading, delamination, acetic acid production and electrode corrosion will occur. In addition to being exposed to ultraviolet light, EVA film may also be exposed to harsh environments with high temperature and high humidity. EVA that is exposed to high temperature and high humidity for a long time will undergo hydrolysis to produce acetic acid. The acetic acid molecules react with the sodium silicate in the glass to produce mobile sodium ions, which leads to the occurrence of potential induced decay. On the other hand, the acetic acid produced by hydrolysis will also corrode the battery cells. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a corrosion-resistant EVA packaging film to solve the above problems.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a corrosion-resistant EVA packaging film, comprising the following components in parts by weight:
[0006] 100 parts of ethylene-vinyl acetate copolymer
[0007] Crosslinking agent 0.8-2 parts
[0008] Antioxidant 0.1-0.3 parts
[0009] Light stabilizer 0.1-0.3 parts
[0010] Silane coupling agent 0.3-3 parts
[0011] Acid scavenger 0.4-1 part.
[0012] As a further embodiment of the present invention, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, wherein the cross-linking curing agent is one or more of cumene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, 4,4-di(tert-amyl peroxy) valeric acid n-butyl ester, peroxy-2-ethylhexyl carbonate tert-butyl ester, 3,3-di(tert-butyl peroxy) ethyl butyrate, or an azo compound; and the auxiliary cross-linking agent is one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, or diethylene glycol dimethacrylate.
[0013] As a further embodiment of the present invention, the antioxidant includes a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol; and the secondary antioxidant is tris(4-nonylphenol) phosphite or tris(2,4-di-tert-butylphenyl) phosphite.
[0014] As a further solution of the present invention, the auxiliary antioxidant is a compound of tris(4-nonylphenol)phosphite and tris(2,4-di-tert-butylphenyl)phosphite, and the mass ratio is 1:1.
[0015] As a further embodiment of the present invention, the silane coupling agent is vinyl tris(2-methoxyethoxy)silane or methacryloxypropyl trimethoxysilane.
[0016] As a further solution of the present invention, the light stabilizer is selected from one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.
[0017] As a further solution of the present invention, the acid scavenger is magnesium hydroxide masterbatch and polycarbodiimide masterbatch, and the weight proportion of the magnesium hydroxide masterbatch or polycarbodiimide masterbatch in the EVA resin is 20%.
[0018] A method for preparing a corrosion-resistant EVA packaging film comprises the following steps: uniformly mixing ethylene-vinyl acetate copolymer, a crosslinking agent, an antioxidant, a light stabilizer, a silane coupling agent and an acid scavenger, and then extruding the EVA packaging film in a single-screw extruder at 95°C.
[0019] As a further solution of the present invention, the thickness of the EVA packaging film is 0.5-0.7 mm.
[0020] Since the present invention adopts the above technical scheme, the present invention has the advantages and positive effects of: the present invention adds an acid scavenger to reduce the acetic acid content of the packaging film after wet heat aging, thereby improving the corrosion resistance of the film; the acid scavenger is selected from magnesium hydroxide and polycarbodiimide, both of which can remove the acetic acid generated by the packaging film under wet heat aging conditions, thereby improving the wet heat aging resistance of the film. DETAILED DESCRIPTION
[0021] Example 1
[0022] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 0.8 parts by weight of a cross-linking agent, 0.1 parts by weight of an antioxidant, 0.1 parts by weight of a light stabilizer, 0.3 parts by weight of a silane coupling agent, and 0.4 parts by weight of an acid scavenger are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.5 mm;
[0023] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent includes isopropyl peroxide and an azo compound, and the auxiliary cross-linking agent is triallyl isocyanurate; the antioxidant includes β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, the auxiliary antioxidant is tris(4-nonylphenol) phosphite, the light stabilizer is 2,4-dihydroxybenzophenone, the silane coupling agent is methacryloxypropyltrimethoxysilane, and the acid scavenger is 0.2 parts by weight of magnesium hydroxide and 0.2 parts by weight of polycarbodiimide masterbatch.
[0024] Example 2
[0025] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 1.2 parts by weight of a cross-linking agent, 0.12 parts by weight of an antioxidant, 0.12 parts by weight of a light stabilizer, 0.8 parts by weight of a silane coupling agent, and 0.6 parts by weight of an acid scavenger are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.6 mm;
[0026] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent is di-tert-butyl peroxide, diisopropylbenzene hydroperoxide and an azo compound, and the auxiliary cross-linking agent is triallyl cyanurate; the antioxidant includes β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester and tri(4-nonylphenol) phosphite; the light stabilizer is 2-hydroxy-4-methoxybenzophenone; the silane coupling agent is vinyl tri(2-methoxyethoxy) silane; the acid scavenger is 0.3 parts by weight of magnesium hydroxide and 0.3 parts by weight of polycarbodiimide masterbatch.
[0027] Example 3
[0028] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 1.5 parts by weight of a cross-linking agent, 0.18 parts by weight of an antioxidant, 0.18 parts by weight of a light stabilizer, 1.5 parts by weight of a silane coupling agent, and 0.7 parts by weight of an acid scavenger are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.6 mm;
[0029] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, wherein the cross-linking curing agent includes 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, 4,4-di(tert-amylperoxy) valeric acid n-butyl ester, peroxy-2-ethylhexyl carbonate tert-butyl ester and azo compounds, and the auxiliary cross-linking agent is trimethylolpropane trimethacrylate; the antioxidant includes a main antioxidant and an auxiliary antioxidant, the main antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester; the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; the light stabilizer is 2-hydroxy-4-methoxybenzophenone and 2-hydroxy-4-n-octyloxybenzophenone; the silane coupling agent is methacryloxypropyl trimethoxysilane; the acid scavenger is 0.3 parts by weight of magnesium hydroxide and 0.4 parts by weight of polycarbodiimide masterbatch.
[0030] Example 4
[0031] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 1.8 parts by weight of a cross-linking agent, 0.24 parts by weight of an antioxidant, 0.24 parts by weight of a light stabilizer, 2.1 parts by weight of a silane coupling agent, and 0.8 parts by weight of an acid scavenger are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.6 mm;
[0032] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent includes tert-butyl peroxide-2-ethylhexyl carbonate and an azo compound, and the auxiliary cross-linking agent is trimethylolpropane trimethacrylate; the antioxidant includes a main antioxidant and an auxiliary antioxidant, the main antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; the auxiliary antioxidant is tri(4-nonylphenol) phosphite; the light stabilizer is 2-hydroxy-4-n-octyloxybenzophenone; the silane coupling agent is vinyl tri(2-methoxyethoxy) silane; the acid scavenger is selected from 0.4 parts by weight of magnesium hydroxide and 0.4 parts by weight of polycarbodiimide masterbatch.
[0033] Example 5
[0034] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 2 parts by weight of a cross-linking agent, 0.3 parts by weight of an antioxidant, 0.3 parts by weight of a light stabilizer, 3 parts by weight of a silane coupling agent, and 1 part by weight of an acid scavenger are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.7 mm;
[0035] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent includes 3,3-di(tert-butylperoxy)butyric acid ethyl ester and an azo compound, and the auxiliary cross-linking agent is diethylene glycol dimethacrylate; the antioxidant includes a main antioxidant and an auxiliary antioxidant, the main antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester; the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; the light stabilizer is 2-hydroxy-4-n-octyloxybenzophenone; the silane coupling agent is methacryloxypropyltrimethoxysilane; the acid scavenger is selected from 0.4 parts by weight of magnesium hydroxide and 0.6 parts by weight of polycarbodiimide masterbatch.
[0036] Comparative Example 1
[0037] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 0.8 parts by weight of a cross-linking agent, 0.1 parts by weight of an antioxidant, 0.1 parts by weight of a light stabilizer, and 0.3 parts by weight of a silane coupling agent are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.5 mm;
[0038] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent includes isopropyl peroxide and an azo compound, and the auxiliary cross-linking agent is triallyl isocyanurate; the antioxidant includes β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, the auxiliary antioxidant is tri(4-nonylphenol) phosphite, the light stabilizer is 2,4-dihydroxybenzophenone, and the silane coupling agent is methacryloxypropyl trimethoxysilane.
[0039] Comparative Example 2
[0040] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 0.8 parts by weight of a cross-linking agent, 0.1 parts by weight of an antioxidant, 0.1 parts by weight of a light stabilizer, 0.3 parts by weight of a silane coupling agent, and 0.4 parts by weight of magnesium hydroxide are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.5 mm;
[0041] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent includes isopropyl peroxide and an azo compound, and the auxiliary cross-linking agent is triallyl isocyanurate; the antioxidant includes β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, the auxiliary antioxidant is tri(4-nonylphenol) phosphite, the light stabilizer is 2,4-dihydroxybenzophenone, and the silane coupling agent is methacryloxypropyl trimethoxysilane.
[0042] Comparative Example 3
[0043] A corrosion-resistant EVA packaging film is prepared by the following method: 100 parts by weight of ethylene-vinyl acetate copolymer, 0.8 parts by weight of a cross-linking agent, 0.1 parts by weight of an antioxidant, 0.1 parts by weight of a light stabilizer, 0.3 parts by weight of a silane coupling agent, and 0.4 parts by weight of a polycarbodiimide masterbatch are uniformly mixed, and then extruded in a single-screw extruder at 95° C. to prepare an EVA packaging film with a thickness of about 0.5 mm;
[0044] Among them, the cross-linking agent includes a cross-linking curing agent and an auxiliary cross-linking agent, the cross-linking curing agent includes isopropyl peroxide and an azo compound, and the auxiliary cross-linking agent is triallyl isocyanurate; the antioxidant includes β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, the auxiliary antioxidant is tri(4-nonylphenol) phosphite, the light stabilizer is 2,4-dihydroxybenzophenone, and the silane coupling agent is methacryloxypropyl trimethoxysilane.
[0045] The film samples of Examples 1-5 and Comparative Examples 1-3 were laminated, and then after wet heat aging (120°C) for 96 hours, one gram of the film was ultrasonically tested in 50 mL of xylene and 25 mL of ethanol for a certain period of time; the film samples of Examples 1-5 and Comparative Examples 1-3 were laminated and the transmittance was tested. The results are shown in Table 1.
[0046] Table 1 is the performance test of Examples 1-5 and Comparative Examples 1-3
[0047] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Acid value 139 116 93 66 42 228 144 152 290-380nm 89.24 88.13 87.26 86.89 85.12 89.84 86.12 87.89 380-1100nm 91.68 91.44 91.32 91.12 90.78 92.17 91.28 91.49
[0048] As shown in Table 1, the acid value measured in Comparative Example 1 without the presence of an acid scavenger is 228 μg KOH per gram of film, the acid value measured in Comparative Example 2 is 144 μg KOH per gram of film when only 0.4 parts by weight of magnesium hydroxide masterbatch is contained, and the acid value measured in Comparative Example 3 is 152 μg KOH per gram of film when only 0.4 parts by weight of polycarboimide masterbatch is contained; it can be seen that after using the acid scavenger, the acid value of the film will decrease, and the corrosion resistance of the film will increase. Compared with the two acid scavengers, the corrosion resistance of magnesium hydroxide will be slightly better. As shown in Table 1, as the amount of acid scavenger (Examples 1-5) gradually increases, the acid value of the film sample gradually decreases. It can be seen from Comparative Examples 2 and 3 that magnesium hydroxide is more likely to affect the transmittance of the film in the ultraviolet region than polycarbodiimide. When the content of magnesium hydroxide in the sample is too high, obvious whitening lines will appear after lamination of the film sample; through implementation 5, it can be found that if the content of the acid scavenger in the film is further increased, the transmittance of the film will be unqualified. In summary, combining the acid value and transmittance of the comparative examples and the embodiments, it can be found that when Example 4 has a higher transmittance, it also has a lower acid value, which shows that the combination of these two acid scavengers can significantly improve the corrosion resistance of the film, avoiding excessive use of magnesium hydroxide, resulting in unqualified transmittance of the film.
[0049] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A corrosion-resistant EVA packaging film, characterized in that: Includes the following Components by weight: 100 parts of ethylene-vinyl acetate copolymer Crosslinking agent 0.8-2 parts Antioxidant 0.1-0.3 parts Light stabilizer 0.1-0.3 parts Silane coupling agent 0.3-3 parts Acid scavenger 0.4-1 part.
2. The corrosion-resistant EVA packaging film according to claim 1, characterized in that: The cross-linking agent comprises a cross-linking curing agent and an auxiliary cross-linking agent. The cross-linking curing agent is one or more of cumene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 4,4-di(tert-amyl peroxy) valeric acid n-butyl ester, peroxy-2-ethylhexyl carbonate tert-butyl ester, 3,3-di(tert-butyl peroxy) ethyl butyrate, or an azo compound; and the auxiliary cross-linking agent is one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane trimethacrylate, or diethylene glycol dimethacrylate.
3. The corrosion-resistant EVA packaging film according to claim 1, characterized in that: The antioxidant comprises a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester; and the secondary antioxidant is tris(4-nonylphenol) phosphite or tris(2,4-di-tert-butylphenyl) phosphite.
4. The corrosion-resistant EVA packaging film according to claim 3, characterized in that: The auxiliary antioxidant is a compound of tris(4-nonylphenol)phosphite and tris(2,4-di-tert-butylphenyl)phosphite, and the mass ratio is 1:
1.
5. The corrosion-resistant EVA packaging film according to claim 1, characterized in that: The silane coupling agent is vinyl tris(2-methoxyethoxy)silane or methacryloxypropyl trimethoxysilane.
6. The corrosion-resistant EVA packaging film according to claim 1, characterized in that: The light stabilizer is selected from one or more of 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.
7. The corrosion-resistant EVA packaging film according to claim 1, characterized in that: The acid scavenger is magnesium hydroxide masterbatch and polycarbodiimide masterbatch, and the weight proportion of the magnesium hydroxide masterbatch or polycarbodiimide masterbatch in the EVA resin is 20%.
8. The corrosion-resistant EVA packaging film according to claim 1, characterized in that: The preparation method of the adhesive film is as follows: after uniformly mixing ethylene-vinyl acetate copolymer, a crosslinking agent, an antioxidant, a light stabilizer, a silane coupling agent and an acid scavenger, extruding the EVA packaging adhesive film in a single-screw extruder at 95° C.
9. The corrosion-resistant EVA packaging film according to claim 8, characterized in that: The thickness of the EVA packaging film is 0.5-0.7 mm.
Citation Information
Cited By
Corrosion-resistant photovoltaic adhesive film for meeting packaging requirement of single-glass assembly DH2000
CN120464336A
High-wear-resistance and corrosion-resistance pipe body lining layer and processing technology thereof
CN120535903A
Self-repairing EVA (Ethylene Vinyl Acetate) adhesive film and preparation method thereof
CN121271465A
Self-repairable EVA adhesive film and preparation method thereof
CN121271465B
